The Evidence of Place in the Poetic Texts of (Abdullah Pashew) - Zhwan Abdul-Salam Azeez Gardi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This research, entitled ((The Evidence of Place in the Poetic Texts of (Abdullah Pashew)), is an attempt to analyze the evidence of having different places and locations in the poets’ poetic texts. Place is an essential element in the construction of (Abdullah Pashew’s) poetry, because there is a deep, strong and interesting meaning embedded in place. Thus, place is not only geometric space, but also roles to produce evidence and a specific meaning. Pashew looks for those places that have strong evidence, fit his purpose(s) and can hit his target. The importance of this research is that place is a constituting component in the poetic text construction and becomes the poet’s message bearer and conveyance. The study adopts (Analytic Description) approach and consists of two sections: the first section theoretically discusses the concept of place, role and importance in poem construction and divided into two sub-sections: in the first sub-section, the concept of place has been discussed in terms of (language, terminology, philosophy, physics and literature). The second sub-section is about the connectedness of place to poetry concerning its importance in the production of the poem and its relation(s) to the language of the poem. While the second section practically deals with the evidence of place in (Abdullah Pashew’s) poetic texts, including: (psychological, political, national, religious, social, historical, civilizational, cultural, symbolic and natural) aspects. The study ends up with some conclusions and a reference list.